2014
DOI: 10.15386/cjm.2014.8872.871.fie1
|View full text |Cite
|
Sign up to set email alerts
|

Ex-Vivo Perfusion Machines in Kidney Transplantation. The Significance of the Resistivity Index

Abstract: IntroductionWith a growing shortage of organs for transplantation, finding ways of increasing the donor organ pool remains of utmost importance. Perfusion machines (PM) have been proven to enhance the potential for kidney transplants to function sooner, last longer, giving patients the opportunity for a better life quality.ObjectiveThe aim of this study is to evaluate the relation between the resistance index provided by the PM, the postoperative resistance index measured by Doppler ultrasound and the initial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…More than that, the vascular resistivity index measured by Doppler ultrasound is correlated with the resistivity index recorded by the life-port perfusion machine used for kidney preservation. It may predict the primary graft outcome [30]. Seiler et al measured resistivity index in different organs of the transplanted patient, including the renal graft, and concluded that RI indicates the presence of systemic vascular pathology, predicting mortality rather than renal graft dysfunction [31], being affected by pulse pressure, frequency and heart rate [32].…”
Section: B Doppler Vascular Ultrasonographymentioning
confidence: 99%
“…More than that, the vascular resistivity index measured by Doppler ultrasound is correlated with the resistivity index recorded by the life-port perfusion machine used for kidney preservation. It may predict the primary graft outcome [30]. Seiler et al measured resistivity index in different organs of the transplanted patient, including the renal graft, and concluded that RI indicates the presence of systemic vascular pathology, predicting mortality rather than renal graft dysfunction [31], being affected by pulse pressure, frequency and heart rate [32].…”
Section: B Doppler Vascular Ultrasonographymentioning
confidence: 99%